The big stampede ; Ride him, cowboy ; Haunted gold [videorecording (DVD)]. - Wright, Tenny, 1885-1971; Allen, Fred, 1896-1955; Wright, Mack V.; Schlesinger, Leon, 1884-1949; Rogell, Sid, 1900-1973; Wayne, John, 1907-1979; Beery, Noah, 1913-1994; Hurst, Paul M.; Madison, Mae; Terry, Sheila; Woods, Harry, 1889-1968; Alderson, Erville, 1882-1957; et al. (Distributed by Warner Home Video, 2006)
The big stampede (1932, 54 min.): A deputy sheriff intervenes when a rustler plots to steal cattle from some New Mexico settlers.